Cold-inducible expression of an Arabidopsis thaliana AP2 transcription factor gene, AtCRAP2, promotes flowering under unsuitable low-temperatures in chrysanthemum - Luo, Chang (Plant physiology and biochemistry : PPB, 2020)
Copyright © 2019 Elsevier Masson SAS. All rights reserved.